2016
DOI: 10.1002/adem.201600606
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Li on Microstructures, Mechanical, and Biocorrosion Properties of Biodegradable Mg94‐xZn2Y4Lix Alloys with Long Period Stacking Ordered Phase

Abstract: Mg 94-x Zn 2 Y 4 Li x alloys (at%) (x ¼ 0, 1, 5, 9, 13) are designed to develop a novel, biodegradable magnesium alloy. Microstructures evolution and mechanical properties are evaluated by using OM, XRD, SEM, and tensile tests. The biocorrosion behaviors of the alloys are investigated by using hydrogen evolution and electrochemical measurements. The precipitation of 18R LPSO phase is facilitated by a little Li (<1 at%), while exceeded Li (>1 at%) inhibits the formation of 18R LPSO phase and favors the formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…An increase in the volume fraction of the Li-containing IMPs promotes filiform corrosion along the grain boundaries and inside the β-Li phase [35]. An increase in the corrosion rate with increasing amounts of Li was reported for Mg-Al-Li, Mg-Zn-Li, Mg-Li-Al-Zn-Y, Mg-Li-Ca, and Mg-Al-Li-Zn alloys [24,26,28,36].…”
Section: Continuous Technological Development and Search For New Ener...mentioning
confidence: 96%
See 1 more Smart Citation
“…An increase in the volume fraction of the Li-containing IMPs promotes filiform corrosion along the grain boundaries and inside the β-Li phase [35]. An increase in the corrosion rate with increasing amounts of Li was reported for Mg-Al-Li, Mg-Zn-Li, Mg-Li-Al-Zn-Y, Mg-Li-Ca, and Mg-Al-Li-Zn alloys [24,26,28,36].…”
Section: Continuous Technological Development and Search For New Ener...mentioning
confidence: 96%
“…The effect of Li concentration on the corrosion resistance of Mg alloys, additionally containing other alloying elements is not so straightforward [16,[24][25][26][27][28][29][30]. Common Mg alloys have various types of intermetallic particles (IMPs) in their microstructure, most of them being cathodic relative to the alloy matrix [16,31,32].…”
Section: Continuous Technological Development and Search For New Ener...mentioning
confidence: 99%
“…The ability of long period stacking ordered (LPSO) phase to enhance mechanical properties has also been investigated [47]. The addition of >1 at.…”
Section: Polymers Composites Alloys and Special Materialsmentioning
confidence: 99%
“…[ 17,18 ] Some researches had reported that LPSO phase can be corrosion barriers to inhibit further corrosion. [ 19,20 ] However, LPSO phase can also act as a local cathode to accelerate corrosion. [ 21 ] This beneficial or detrimental effect may be achieved by the second phases, with varying chemical composition and microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…[ 22 ] Alloying treatment is an efficient approach to restrict grain growth and to control small second phase at grain boundaries during solidification. [ 23 ] Therefore, there were an increasing number of researches about alloying element, such as Li [ 19 ] and Mn. [ 20 ]…”
Section: Introductionmentioning
confidence: 99%